Behavioral variant frontotemporal dementia patients do not succumb to the Allais paradox - Bertoux, Maxime; Cova, Florian; Pessiglione, Mathias; Hsu, Ming; Dubois, Bruno; Bourgeois-Gironde, Sacha (Frontiers in Neuroscience, 2014)
The Allais Paradox represents on of the earliest empirical challenges to normative models of decision-making, and suggests that choices in one part of a gamble may depend on the possible outcome in another, independent, part of the gamble—a violation of the so-called “independence axiom”. To account for Allaisian behavior, one well-known class of models propose that individuals’ choices are influenced not only by possible outcomes resulting from one’s choices, but also the anticipation of regret for foregone options. Here we test the regret hypothesis using a population of patients with behavioral variant frontotemporal dementia (bvFTD), a clinical population known to present ventromedial prefrontal cortex dysfunctions and associated with impaired regret processing in previous studies of decision-making. Compared to behavior of matched controls and Alzheimer (AD) patients that has no ventromedial prefrontal atrophy, we found a striking diminution of Allaisian behavior among bvFTD patients. These results are consistent with the regret hypothesis and furthermore suggest a crucial role for prefrontal regions in choices that typically stands in contradiction with a basic axiom of rational decision-making.